Periodistas de película. La imagen de la profesión periodística a través del cine - Mera Fernández, Montse (Estudios sobre el Mensaje Periodístico, 2008)
According to different research from Spain and USA, the journalistic profession doesn’t go through its best moment. Society’s distrust of the function fulfilled by journalists, causes professionals frustration, who in addition to its increasing unstable labour condition, have to see frequently how their image shown in cinema and television is too much unfavourable. In this article we try to show which journalist vision has been offered to the society through cinema.